Biomass and Soil Nutrients Turnover Affected by Different Peat Vegetation - M Edi Armanto; Agus Hermawan; Momon Sodik Imanudin; Elisa Wildayana; Sukardi Sukardi; Arjuna Neni Triana (Journal of Wetlands Environmental Management, 2023)
This research aimed to analyze potential supply and removal of biomass and soil nutrients induced by different vegetation on peatlands. The research was carried out in peats dome of the catchment area of the Sibumbung River and the Burnai River in Pedamaran Sub-Districts, OKI South Sumatra. The research method used field survey of case studies of four natural phenomena (swamp grass, bush swamp, pulai peatlands, and peat forest). The research resulted that the highest production and harvest of biomass came from peat forest, pulai peatland, bush swamp and swamp grass. The highest biomass supply to the soils were given by the peat forest, pulai peatland, bush swamp and swamp grass (around 12,545; 11,593; 7,491 and 5,313 kg/ha/year respectively). The more varied the vegetation type, the higher the supply of soil nutrients. Swamp grass and bush swamp have low vegetation diversity and are mostly dominated by alang-alang. Swamp grass and bush swamp showed the same pattern and the order of nutrient supply in the highest sequence is K, Ca, N, Mg, Ca, and P. The supply order of soil nutrients (peat forest and pulai peatland) showed a similar pattern, namely from the highest content of Ca, N, K, Mg and P. Pulai vegetation can be recommended for a paludiculture system because it resembles almost the peat forest in producing biomass and soil nutrient supply to the soils and is originally native plant from peatland.